PENDAMPINGAN PASTORAL KONSELING KEPADA LANSIA YANG TERPINGGIRKAN - Gita Yuventia Rauf (MATHESI: Jurnal Pendidikan dan Bimbingan Konseling, 2026)
Elderly individuals, particularly widows, often face social isolation and multidimensional poverty, which trigger profound grief and the loss of economic protection. This descriptive qualitative study aims to provide a deep and humane portrayal of the life reality and inner needs of a 70-year-old widow in Buha Village. The subject carries a heavy physical and psychological burden as the family’s primary breadwinner by selling cakes, yet she possesses strong spiritual resilience through her habit of reading the Bible. A Client-Centered approach is employed in pastoral action to assist the subject in mapping problems, setting priorities, and empowering her self-potential to ensure her mental health and dignity remain intact. Overall, pastoral counseling plays a vital role in restoring the holistic well-being of the elderly through the functions of healing, sustaining, guiding, empowering, and transforming. The success of this service relies heavily on the synergy between spiritual compassion and the competence of certified professional counselors to ensure the guidance is ethical and accountable. Through this process, the subject is encouraged to rediscover her self-worth as a valuable individual before God and society, enabling her to live her old age with greater tranquility and independence.